Respiratory Protection for Healthcare Workers - Estella Whimbey; Timothy Dellit; Mary Dessel (Association of American Medical Colleges, 2012)
Abstract This training module covers the respiratory protection of health care workers. Learners get an overview of airborne and droplet-transmitted infections, reinforced by case studies of significant health care associated outbreaks of infections. Must-have respiratory protection precautions are presented, including respiratory hygiene and etiquette; droplet and airborne infection control precautions; administrative and environmental controls to prevent the acquisition and transmission of infections; and the proper selection and use of personal protective equipment including the proper selection, fitting, and use of respirators and masks. There was an institutional need to deliver respiratory protection training to medical staff. It was decided that an online learning module would be created and rolled out through the organization's learning management system. Positive feedback and good completion rates were obtained in the pilot project. As a result, our internal graduate medical education committee approved this online module as mandatory training for all incoming residents, and this module is currently proposed to be part of the quality and safety curriculum across the organization.